Influence of wetland borders on prevalence of fall armyworm and wasps in maize-soybean cropping system in Eastern Uganda - Ojuu, David; Kyamanywa, Samuel; Odong Lapaka, Thomas (International Journal of Pest Management, 2021)
The non-crop habitats within agro-ecosystems are important resources for ecological and biological insect pest management. Diversified cropping systems are known to influence pest populations, however, how neighboring habitats affect pest population dynamics is not clear. This study focused on understanding the influence of wetland borders on Fall Armyworm (FAW) and wasps prevalence in a maize-soybean intercrop system in Eastern Uganda. FAW and wasps population estimates were carried out in twelve farmers’ fields stratified within 0–300 and 500–1100 meters from the wetland borderline. Data were collected biweekly from emergence until post flower growth of the crops. Results showed the prevalence of FAW was significantly higher on maize-soybean fields 500–1100 meters compared to those within 0 to 300m from the wetland borders. While the prevalence of wasps was significantly higher in the crops at 82–219 meters from wetland borderline. It is concluded that wetland borders play a crucial role in negatively affecting crop pest populations while positively influencing natural enemy populations and these effects are influenced by distance of crop fields from the wetland border.
Keywords: Wetland borders; Fall armyworm; Wasps; Population estimates; Maize-soybean intercrop